Prevalence of adult ADHD among surgical trainees: a cross-sectional study from a Turkish University Hospital - Gonca Ayse Unal; Selin Balki Tekin; Ayse Nur Inci Kenar (BMC Medical Education)
Abstract Background The similarities between the clinical symptoms and temperament characteristics of individuals with attention deficit hyperactivity disorder (ADHD) and the surgical personality are noteworthy and the ADHD research in surgeons has remained neglected. In this study, the aim was to investigate the frequency of adult ADHD in Turkish surgical trainees and its effects on their medical branch selection. Methods The 114 participants in the study were evaluated using a Sociodemographic Data Form, which included factors affecting the choice of surgical branches, and the Adult ADD/ADHD DSM IV-Based Diagnostic Screening and Rating Scale. Results 32.5% of the participants were female, 66.7% were male. The mean age of the participants was 28.21 ± 2.43. Adult ADHD symptoms were found in 31.6% of the surgeons, of which n = 13(36.1%) were the inattentive subtype, n = 14(38.9%) were the hyperactivity subtype and n = 9(25.0%) were the combined subtype. While a statistically significant difference was found between departments in terms of inattention subtypes (p = 0.003), no statistically significant difference was found in terms of hyperactivity subtype (p > 0.005). Conclusions This study highlights that ADHD is common among surgical trainees and its assessment may be significant. It was hypothesized that surgical trainees with ADHD may have chosen the field of surgery as a way of coping with the disorder. It was thought that the demanding nature of surgical work may provide a favourable environment for those with ADHD, allowing them to channel their innate characteristics into a focused and goal-directed pursuit. Trial registration Clinical trial number: not applicable.